Volume 3: Cycle Innovations; Education; Electric Power; Fans and Blowers; Industrial and Cogeneration 2012
DOI: 10.1115/gt2012-68697
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Supercritical CO2 Closed Regenerative Brayton Cycle in a Bench Scale Experiment

Abstract: Power generation with a supercritical CO2 closed regenerative Brayton cycle has been successfully demonstrated using a bench scale test facility. A set of a centrifugal compressor and a radial inflow turbine of finger top size is driven by a synchronous motor/generator controlled using a high-speed inverter. A 110 W power generating operation is achieved under the operational condition of rotational speed of 1.15kHz, CO2 flow rate of 1.1 kg/s, and respective thermodynamic states (7.5 MPa, 304.6 K) at compresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…compressor geometry, careful consideration is required when designing the SeCO 2 compressor. From the previous research works, it has been consistently shown that the compressor efficiency was significantly affected by the windage loss and the system operation was influenced by the thrust load balancing [17,20,21]. Therefore, the development of SCIEL requires step-bystep construction approach while examining the component (especially turbomachinery) performance carefully at each stage.…”
Section: Objectives and Design Basis Of Seco 2 Integral Experiments Loopmentioning
confidence: 98%
See 3 more Smart Citations
“…compressor geometry, careful consideration is required when designing the SeCO 2 compressor. From the previous research works, it has been consistently shown that the compressor efficiency was significantly affected by the windage loss and the system operation was influenced by the thrust load balancing [17,20,21]. Therefore, the development of SCIEL requires step-bystep construction approach while examining the component (especially turbomachinery) performance carefully at each stage.…”
Section: Objectives and Design Basis Of Seco 2 Integral Experiments Loopmentioning
confidence: 98%
“…First of all, it was determined from the first design phase, the recompressing (split-flow) process is not planned to be demonstrated in SCIEL due to the limit in infrastructure capacity. In the previous studies, the recompressing process is discarded due to the small power size [7,17]. However, the recompressing layout will be considered for the long-term goal to further resolve turbomachinery design, operation and control issues in the sophisticated cycle layout.…”
Section: Objectives and Design Basis Of Seco 2 Integral Experiments Loopmentioning
confidence: 99%
See 2 more Smart Citations
“…But neither of them did a 3D calculation for their design results. There are also many other universities and research institutes that have carried out relevant research on the design strategy of SCO 2 compressors [7][8][9][10][11][12] and some research institutes have carried out experiments [13][14][15]. More recently, Rinaldi (2014) and colleagues utilized an in-house fluid dynamic solver and simulated the test compressor of Sandia National Laboratories (SNL) based on the steady state method [16].…”
Section: Introductionmentioning
confidence: 99%